1998
DOI: 10.1016/s0969-2126(98)00152-x
|View full text |Cite
|
Sign up to set email alerts
|

Sheep liver cytosolic aldehyde dehydrogenase: the structure reveals the basis for the retinal specificity of class 1 aldehyde dehydrogenases

Abstract: . The submicromolar Km of ALDH1 for all-trans retinal, and its 600-fold enhanced affinity for retinal compared to acetaldehyde, are explained by the size and shape of the substrate entrance tunnel in ALDH1. All-trans retinal fits into the active-site pocket of ALDH1, but not into the pocket of ALDH2. Two helices and one surface loop that line the tunnel are likely to have a key role in defining substrate specificity in the wider ALDH family. The relative sizes of the tunnels also suggest why the bulky alcohol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
263
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 201 publications
(278 citation statements)
references
References 59 publications
14
263
1
Order By: Relevance
“…After the hydride transfer, the reduced nicotinamide ring must exit the catalytic site to allow for the accessibility of a water molecule, which hydrolyzes the acyl-sulfur bond releasing the product. In agreement with this mechanism, numerous crystal structures of ALDH revealed two common conformations of the coenzyme, depending on its oxidation state: the extended ("hydride transfer") conformation of NAD(P) ϩ , with the nicotinamide ring positioned close to Cys-302; and the contracted ("hydrolysis") conformation of NAD(P)H, with the nicotinamide ring found outside of the catalytic site or disordered (4,5,7,10,25,27,30). The mechanism by which ALDHs sense the oxidation state of the bound coenzyme and control its conformation is not fully understood.…”
mentioning
confidence: 76%
See 4 more Smart Citations
“…After the hydride transfer, the reduced nicotinamide ring must exit the catalytic site to allow for the accessibility of a water molecule, which hydrolyzes the acyl-sulfur bond releasing the product. In agreement with this mechanism, numerous crystal structures of ALDH revealed two common conformations of the coenzyme, depending on its oxidation state: the extended ("hydride transfer") conformation of NAD(P) ϩ , with the nicotinamide ring positioned close to Cys-302; and the contracted ("hydrolysis") conformation of NAD(P)H, with the nicotinamide ring found outside of the catalytic site or disordered (4,5,7,10,25,27,30). The mechanism by which ALDHs sense the oxidation state of the bound coenzyme and control its conformation is not fully understood.…”
mentioning
confidence: 76%
“…Catalytic Glutamate Is Critical for Mobility and Correct Positioning of Coenzyme-Several studies have suggested that the invariant catalytic glutamate of ALDHs (Glu-268 in class 1 and 2 enzymes) participates in both acylation and deacylation stages of the ALDH catalysis (5,7,23,25). Specifically, it has been proposed that in the first step it deprotonates the catalytic cysteine prior to nucleophilic attack on the substrate, whereas in the second step it activates a water molecule to facilitate the hydrolysis of the acyl-enzyme intermediate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations